Efficiency Enhancement of Banana Peel for Waste Water Treatment through Chemical Adsorption: Efficiency of Banana Peel for Waste Water Treatment - Khan, Atif; Naqvi, Hassan Jived; Afzal, Shabana; Jabeen, Shaista; Iqbal, Misbah; Riaz, Iram (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Many types of agricultural wastes are now being studied for waste water treatment because of their adsorbing properties. For instance, banana peels are capable of adsorbing various metals and other pollutants present in industrial waste waters, provided the peels are pretreated with proper surface-active agents. This manuscript reports an investigation regarding activation of banana peels for this purpose. Banana peels were treated with dilute solutions of oxalic acid, sulfuric acid and sodium hydroxide at room temperature for 24 hours followed by drying at 90°C. The adsorbing properties of banana peels were studied by using Fourier’s transform infrared spectroscopy (FT-IR). It was observed that FT-IR is a quick and simple technique to verify the surface activation of banana peels.